Revisiting Employee Engagement: A Systematic Review of Emerging Perspectives - Roosendy Annisa Putri; Fiona Niska Dinda Nadia (Eduvest - Journal of Universal Studies, 2026)
This research aims to explore the conceptual shift in the meaning of employee engagement through a systematic literature review (SLR) approach based on the PRISMA protocol. The review analyzes 17 selected articles published between 2006 and 2025 to identify the evolving dynamics of understanding, influencing factors, and approaches to fostering employee engagement. The findings indicate that employee engagement is no longer narrowly understood as mere attachment to job tasks or roles but has evolved into a multidimensional construct influenced by personal values, sustainability, digitalization, and the new generation’s expectations for meaningful work. The review also reveals that organizational support, leadership quality, and technology integration have become increasingly prominent factors in shaping employee engagement. The theoretical implications highlight the need for a new, more adaptive and contextual conceptual model, while the practical implications point to the importance of value-based, employee-experience-driven human resource management strategies. This study contributes to enriching the understanding of engagement in the ever-evolving modern work landscape.